Phase I Study of Nintedanib Incorporating Dynamic Contrast‐Enhanced Magnetic Resonance Imaging in Patients With Advanced Solid Tumors. (20th March 2015) - Lee, Chooi Peng; Taylor, N. Jane; Attard, Gerhardt; Pacey, Simon; Nathan, Paul D.; de Bono, Johann S.; Temple, Graham; Bell, Susan; Stefanic, Martin; Stopfer, Peter; Tang, Adrian; Koh, Dow‐Mu; et al.
Abstract : Background: This open‐label phase I dose‐escalation study investigated the safety, efficacy, pharmacokinetics (PK), and dynamic contrast‐enhanced magnetic resonance imaging (DCE‐MRI) effects of the oral angiokinase inhibitor nintedanib in patients with advanced solid tumors. Methods: Nintedanib was administered once daily continuously, starting at 100 mg and later amended to allow evaluation of 250 mg b.i.d. The primary endpoint was maximum tolerated dose (MTD). DCE‐MRI studies were performed at baseline and on days 2 and 28. Results: Fifty‐one patients received nintedanib 100–450 mg once daily ( n = 40) or 250 mg b.i.d. ( n = 11). Asymptomatic reversible liver enzyme elevations (grade 3) were dose limiting in 2 of 5 patients at 450 mg once daily. At 250 mg b.i.d., 2 of 11 patients experienced dose‐limiting toxicity (grade 3 liver enzyme elevation and gastrointestinal symptoms). Common toxicities included fatigue, diarrhea, nausea, vomiting, and abdominal pain (mainly grade ≤2). Among 45 patients, 22 (49%) achieved stable disease; 7 remained on treatment for >6 months. DCE‐MRI of target lesions revealed effects in some patients at 200 and ≥400 mg once daily. Conclusion: Nintedanib is well tolerated by patients with advanced solid malignancies, with MTD defined as 250 mg b.i.d., and can induce changes in DCE‐MRI. Disease stabilization >6 months was observed in 7 of 51 patients. Abstract : 摘要 背景 . 本次开放标签、增量I期研究探索了口服血管激酶抑制剂尼达尼布治疗进展期实体瘤患者的安全性、有效性、药代动力学（PK）以及动态对比增强核磁共振成像（DCE‐MRI）的应用效果。 方法 . 尼达尼布每日1次连续使用，起始剂量为100 mg，随后修正为250 mg，每日2次。主要终点为最大耐受剂量（MTD）。基线期以及第2和28天进行DCE‐MRI分析。 结果 . 51例患者接受了尼达尼布100 ∼ 450 mg（ n = 40），每日1次，或250 mg，每日2次（ n = 11）。在450 mg每日1次剂量水平，2/5例患者发生无症状性可逆性肝酶学指标升高（3级）。在250 mg每日2次剂量水平，2/11例患者发生剂量限制性毒性反应（3级肝酶学指标升高和胃肠道症状）。常见的毒性反应包括乏力、腹泻、恶心、呕吐以及腹痛（大多为≤ 2级）。45例患者中，22例（49%）达到疾病稳定状态；7例维持治疗> 6个月。在200 mg和≥ 400 mg每日1次剂量水平，部分患者DCE‐MRI靶向病灶显示出有效性。 结论 . 尼达尼布在进展期实体瘤患者中耐受性良好，MTD确定为250 mg，每日2次，该剂量能够诱导DCE‐MRI的变化。51例患者中有7例疾病稳定> 6个月。 The Oncologist 2015;20:368–369